The role of kidney in the inter-organ coordination of endogenous glucose production during fasting - Keizo Kaneko; Maud Soty; Carine Zitoun; Adeline Duchampt; Marine Silva; Erwann Philippe; Amandine Gautier-Stein; Fabienne Rajas; Gilles Mithieux (Elsevier, 2018)
Objective: The respective contributions to endogenous glucose production (EGP) of the liver, kidney and intestine vary during fasting. We previously reported that the deficiency in either hepatic or intestinal gluconeogenesis modulates the repartition of EGP via glucagon secretion (humoral factor) and gut-brain-liver axis (neural factor), respectively. Considering renal gluconeogenesis reportedly accounted for approximately 50% of EGP during fasting, we examined whether a reduction in renal gluconeogenesis could promote alterations in the repartition of EGP in this situation. Methods: We studied mice whose glucose-6-phosphatase (G6Pase) catalytic subunit (G6PC) is specifically knocked down in the kidneys (K-G6pc-/- mice) during fasting. We also examined the additional effects of intestinal G6pc deletion, renal denervation and vitamin D administration on the altered glucose metabolism in K-G6pc-/- mice. Results: Compared with WT mice, K-G6pc-/- mice exhibited (1) lower glycemia, (2) enhanced intestinal but not hepatic G6Pase activity, (3) enhanced hepatic glucokinase (GK encoded by Gck) activity, (4) increased hepatic glucose-6-phosphate and (5) hepatic glycogen spared from exhaustion during fasting. Increased hepatic Gck expression in the post-absorptive state could be dependent on the enhancement of insulin signal (AKT phosphorylation) in K-G6pc-/- mice. In contrast, the increase in hepatic GK activity was not observed in mice with both kidney- and intestine-knockout (KI-G6pc-/- mice). Hepatic Gck gene expression and hepatic AKT phosphorylation were reduced in KI-G6pc-/- mice. Renal denervation by capsaicin did not induce any effect on glucose metabolism in K-G6pc-/- mice. Plasma level of 1,25 (OH)2 D3, an active form of vitamin D, was decreased in K-G6pc-/- mice. Interestingly, the administration of 1,25 (OH)2 D3 prevented the enhancement of intestinal gluconeogenesis and hepatic GK activity and blocked the accumulation of hepatic glycogen otherwise observed in K-G6pc-/- mice during fasting. Conclusions: A diminution in renal gluconeogenesis that is accompanied by a decrease in blood vitamin D promotes a novel repartition of EGP among glucose producing organs during fasting, featured by increased intestinal gluconeogenesis that leads to sparing glycogen stores in the liver. Our data suggest a possible involvement of a crosstalk between the kidneys and intestine (via the vitamin D system) and the intestine and liver (via a neural gut-brain axis), which might take place in the situations of deficient renal glucose production, such as chronic kidney disease. Keywords: Endogenous glucose production, Gluconeogenesis, Hypoglycemia, Glycogen, Chronic kidney disease, Vitamin D